Individual, Social, and Workplace Perspectives: Trends in the Misuse of Local Government Assets - Muhammad Iqbal; Rahma Masdar; Muhammad Din; Masruddin Masruddin; Yuldi Mile; Daud Ruranto Buntulabi; Andi Mappanyukki (DINASTI RESEARCH, 2026)
Fraud in public-sector asset management has traditionally been explained primarily through individual-level factors, while the influence of organizational and social contexts has received comparatively limited attention. This study examines how rationalization, peer influence, moral intensity, and the psychosocial work environment jointly shape fraud propensity in local government asset management. A quantitative survey was conducted among asset management officials from 39 provincial government work units in Central Sulawesi, Indonesia. Using purposive sampling, 114 valid responses were collected and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis demonstrates that rationalization and peer influence significantly increase fraud propensity, whereas moral intensity and a favorable psychosocial work environment reduce employees’ tendency to engage in fraudulent behavior. In addition, rationalization negatively affects the psychosocial work environment, while moral intensity contributes positively to employees’ perceptions of workplace psychosocial conditions. These results extend conventional fraud literature by integrating Fraud Triangle Theory and Attribution Theory, demonstrating that fraud propensity is shaped not only by individual cognitive processes but also by social influences and organizational conditions. The findings highlight the importance of strengthening psychosocial workplace conditions, ethical awareness, and positive peer relationships as complementary strategies for reducing fraud risk in public-sector asset management.